Unsur Kebudayaan Di Desa Wisata Kapal Kecamatan Mengwi Kabupaten Badung Sebagai Daya Tarik Wisata - Nurprasetya, Muhammad Revandhika; Anom, I Putu (JURNAL DESTINASI PARIWISATA, 2024)
Desa Wisata is one of tourism variety that is starting to gain attention. The cultural practices of the people who live in the village are the main attraction for tourists. One of them is Desa Kapal which is a desa wisata located in Badung and famous for Aci Tabuh Rah Pengangon. This study is to identify seven elements of universal culture according to Koentjaraningrat existing in Desa Wisata Kapal and have potential to be tourist attraction. This study uses a qualitative approach method. Collection using observation of research locations, in-depth interviews, and literature studies. The results of this study include seven cultural elements in Desa Kapal starting from the language used, products from living equipment and technology, social systems that exist in society, knowledge that grows in people's lives, people's livelihoods to make a living, religion adhered to as well as the ceremonies and rituals performed, and the arts that developed in Desa Kapal. Several potential tourist attractions in Desa Kapal are pottery, Aci Tabuh Rah Pengangon, and arts. Based on the research results, it is concluded that Desa Kapal is a village with unique and interesting cultural diversity. With the potential they have, the stakeholders can carry out several program activities for tourists which aim to introduce the culture that exists in the Desa Kapal community so that a sense of respect and love for culture is created in the Desa Kapal. Keywords: 7 Unsur Kebudayaan Universal, Kebudayaan, Desa Wisata, Desa Wisata Kapal, Aci Tabuh Rah Pengangon